2020
DOI: 10.2147/copd.s275234
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pain Prevalence, Localization, and Intensity in Adults with and without COPD: Results from the Danish Health and Morbidity Survey (a Self-reported Survey)</p>

Abstract: Introduction Pain is a clinical complication to chronic obstructive pulmonary disease (COPD) that interferes negatively with physical activity level (PAL), quality of life (QOL) and pulmonary interventions. Yet, research in pain characteristics including prevalence, localization, and intensity in people with COPD are sparsely researched. Aim To investigate self-reported pain prevalence, localization and intensity of pain in people with and without COPD, and to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…One question concerns body mass index (BMI) and is usually self-scored but we calculated this using data collected at the same time as the pulmonary function tests. The Kihon Checklist total score, which is a sum of 25 answers, ranges from 0 (no frailty) to 25 (severe frailty) and patients' frailty status was classified as robust (0-3), pre-frail (4-7) and frail (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), as reported in the literature [28,39,40].…”
Section: Assessment Of Fatigue Pain Breathlessness and Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…One question concerns body mass index (BMI) and is usually self-scored but we calculated this using data collected at the same time as the pulmonary function tests. The Kihon Checklist total score, which is a sum of 25 answers, ranges from 0 (no frailty) to 25 (severe frailty) and patients' frailty status was classified as robust (0-3), pre-frail (4-7) and frail (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), as reported in the literature [28,39,40].…”
Section: Assessment Of Fatigue Pain Breathlessness and Frailtymentioning
confidence: 99%
“…Prevalence rates for pain have also been reported to be surprisingly high in subjects with COPD over the last decade [8][9][10][11][12][13][14][15][16][17]. In a systematic review published in 2015, Lee et al reported that the pooled prevalence of pain in moderate to very severe COPD was 66% (95% CI, 44-85%) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 43.7% of COPD patients experienced back pain. Additionally, HajGhanbari et al reported that pain was 2.2 and 7.5 times more common in COPD patients than in age‐ and sex‐matched individuals without COPD 24 …”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…The parts of the body affected by pain can include the trunk, neck, shoulder, chest, and back areas, and the most common location of pain can vary among COPD patients 25 . Although the connection between pain intensity and COPD is still unclear, HajGhanbari et al showed that pain intensity and interference scores were significantly higher in patients with COPD than in those without COPD 24 . However, Bentsen et al revealed that there are no significant differences in pain intensity between COPD patients and the general population 26 .…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…26 Similar bidirectional association was also observed between pain and negative emotion. 27 This association of poor sleep quality with body pain has been usually observed in general population 28 as well as patients with lung cancer 29 and COPD, 30 but rarely in patients with mild COPD. According to a nationwide prevalence study in China, among adults with COPD, 56.4% had mild disease (GOLD 1) and only 7.4% had severe or very severe disease (GOLD 3 and GOLD 4).…”
Section: Introductionmentioning
confidence: 96%